Theoretical proton affinities of alpha1 adrenoceptor ligands - KINSELLA, GEMMA; ROZAS, ISABEL; WATSON, GRAEME WILLIAM (My University, 2006)
A systematic study has been performed of the proton affinity of a large family of agonists and antagonists of the ?1-adrenoceptor at the B3LYP/6-31G* level of theory. After a conformational search, all the N atoms were considered as protonation sites and protonation energy values were determined. The inclusion of solvation by means of the Onsager model yielded stabilization in the proton affinity values obtained. In addition, a good correlation was found between the proton affinity values corresponding to the first protonation in gas phase of some of the compounds and their corresponding experimental affinity constants Ki for the ?1A adrenergic receptor.
PUBLISHED
Keywords: Adrenoceptor; ?1; Density Functional Theory; Proton affinity; alpha1